Radiocesium concentrations in wild reindeer at Dovrefjell, Norway - Skogland, Terje (Rangifer, 1987)
Seasonal radiocesium concentrations varied about 6 times in wild reindeer following the Chernobyl accident, from 8 KBq/kg in August to 46 KBq/kg in March. These results agree with the predictions of earlier models. The within-season coefficient of variation was 52-62%. Between one half and 3/4 of this variation was explained by altitudinal and geographical factors, i.e. a 5-fold increase in concentrations from the westernmost to the easternmost locations across the watershed at Dovrefjell, and a 6-fold increase in concentrations from feeding locations in the subalpine to the high alpine zone in autumn. The positive correlation with altitude was reversed in winter for animals foraging in the subalpine coniferous zone on arboreal lichens.Radiocesium-konsentrasjoner hos villrein på Dovrefjell, Norge.Abstract in Norwegian / Sammendrag: Konsentrasjonene»av radiocesium hos villrein gjennom sesongene som fulgte Tsjernobyl-ulykken varierte meget, fra 8 KBq/kg i august til 46 KBq/kg i mars. Disse resultater samsvarer med hva som kunne forutsies i tidlige modeller. Variasjonskoeffisienten innen sesong var 52-62%. Mellom halvdelen og tre fjerdedeler av variasjonen kunne forklares fra høydemessige og geografiske faktorer, d.v.s. en 5-foldig økning i konsentrasjonen fra den vestligste til de østligste lokaliseringer over vannskillet på Dovrefjell og en 6-foldig økning i konsentrasjonene fra beitelokaliseringer fra den subalpine til den høyalpine sone om høsten. Den positive korrelasjon med høyden ble snudd om vinteren for dyr som beitet på skjegglav i den subalpine bar-skogsone.
Keywords: rangifer; wild reindeer; Dovrefjell; Norway; radiocesium